Custom-Made Antibiotic Cement-Coated Nail for the Treatment of Infected Bone Defect. (5th March 2021) - Wang, Guoliang; Luo, Wen; Zhou, Yong; Zhu, Zhenfeng; Zhao, Zihou; Liu, Shiyu; Li, Jing; Feng, Xuebin; Zheng, Yao; Liang, Jiahe; Yi, Jiangpu; Zhang, Yong; et al.
Abstract : Background . Longbone infected bone defect remains a great challenge due to multiple surgeries, long-term treatment duration, and uncertain prognosis. Treatment principles include eradication/debridement, stabilization, and antibiotic administration. An antibiotic cement-coated nail has shown great prospects due to both local antibiotic elution and stabilization of bone defects. However, the current fabrication technique remains to be improved. Methods . For the first time, we described a new method for custom-made cement-coated nail fabrication based on a 3D printing technique. A retrospective study of 19 consecutive patients with long bone infected bone defects from one medical center was conducted who met the inclusion and exclusion criteria from November 2016 to May 2020. The treatment involved thorough debridement, custom-made antibiotic cement-coated nail filling, and culture-specific systemic antibiotic treatment guided by a multidisciplinary team. Clinical and radiographic examinations (X-ray and CT scans) were used to evaluate bony union. Clinical and laboratory examinations were used to evaluate the infection control. The SF-36 score was used to evaluate patients' quality of life pre- and postoperatively. Results . The mean follow-up was 98.8 weeks (ranging from 40 to 192). All cases achieved infection control, 3 cases achieved bone healing after one-stage operation, and 12 cases achieved bone healing after a two-stage bone graft procedure. At the last follow-up, none of the 19 patients had infection recurrence or 1 case had failure of the protective plate. The pre- and postoperative SF-36 score showed that there were statistical differences in all the 9 aspects. Conclusions . The precise custom-made antibiotic cement-coated intramedullary nail through the 3D printing technique used in this study is an effective strategy for the treatment of infected bone defects of long bone. This technique may help to increase the infection control rate and promote bone healing.